Effectiveness of BPHTB Verification and Validation Process for Land and Buildings in Bekasi City - Ambhara Reyhan Anfeis; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
The existence of BPHTB acceptance by the government, especially the Regional Government, cannot be separated from the important role of a Notary who has the authority as a Land Deed Maker Officer or commonly known as PPAT. BPHTB is an obligation to pay taxes incurred due to a transfer of rights to land and buildings that must be paid by the buyer. A transfer of rights to land and buildings can only be carried out if it is carried out in the presence of a PPAT. Notaries such as PPATs are important parties in the acceptance of BPHTB to the Regional Government because in order to make BPHTB payments by taxpayers a BPHTB registration process is required first, which can only be done by a Notary as PPAT. Although BPHTB payments can be made independently by taxpayers, this cannot be done without BPHTB registration carried out by a Notary as PPAT. From the explanation above, we can find one of the important roles of a Notary as a PPAT in the process of tax revenue and income, especially the BPHTB tax as one of the local government revenues. The reality in the field is that the Regional Government does not realize the important role of the Notary as the PPAT in the process of accepting the BPHTB. The Regional Government is passive and not appreciative of the Notary as the PPAT so as not to create a mutualistic relationship between the Regional Government and the Notary as the PPAT.